Public Policy and Rural Development: Assessing the Impact of CSDA in Edo State, Nigeria - Ebonine, Victor Chukwugekwu; Kadiri, John Aigbojie (LPPM Universitas Jambi, 2026)
This study evaluates the impact of the Community and Social Development Agency (CSDA) on rural development in Edo State, Nigeria. Using a qualitative research design, data were collected through in-depth interviews with 109 participants, including CSDA officials and community members selected via random and convenience sampling. Thematic analysis reveals that rural communities are actively involved in project execution through counterpart funding, labor, and supervision. The findings demonstrate that CSDA interventions significantly improved socio-economic activities and local security, proving the effectiveness of community-driven approaches over traditional top-down models. This research contributes to the literature by providing empirical evidence from an underexplored region, highlighting the sustainability of people-centered development. The results offer practical policy implications for addressing rural underdevelopment through participatory strategies. Future studies are encouraged to adopt mixed-methods approaches to further validate these grassroots dynamics.